2001
DOI: 10.1021/ja004307+
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Mn-Centered Oxidation in the S2 → S3 Transition:  Implications for the Mechanism of Photosynthetic Water Oxidation

Abstract: A key question for the understanding of photosynthetic water oxidation is whether the four oxidizing equivalents necessary to oxidize water to dioxygen are accumulated on the four Mn ions of the oxygen-evolving complex (OEC), or whether some ligand-centered oxidations take place before the formation and release of dioxygen during the S 3 → [S 4 ] → S 0 transition. Progress in instrumentation and flash sample preparation allowed us to apply Mn Kβ X-ray emission spectroscopy (Kβ XES) to this problem for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

55
488
3
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(552 citation statements)
references
References 128 publications
55
488
3
4
Order By: Relevance
“…Mn(1)ZIV, Mn(2)ZIV, Mn(3)ZIII, Mn(4)ZIII) and model (b) where an additional water ligand is completing the hexacoordinated shell of Mn(4) and the oxidation states are Mn 4 (IV,III,III,IV ). These results are partially consistent with EPR and X-ray spectroscopic evidence (Ono et al 1992;Yachandra et al 1993;Roelofs et al 1996;Bergmann et al 1998;Iuzzolino et al 1998;Dau et al 2001;Messinger et al 2001) but disagree with the suggested low-valent Mn 4 (III,III,III,III ) state (Zheng & Dismukes 1996;Kuzek & Pace 2001).…”
Section: Structural Models Of the O 2 -Evolving Centresupporting
confidence: 49%
“…Mn(1)ZIV, Mn(2)ZIV, Mn(3)ZIII, Mn(4)ZIII) and model (b) where an additional water ligand is completing the hexacoordinated shell of Mn(4) and the oxidation states are Mn 4 (IV,III,III,IV ). These results are partially consistent with EPR and X-ray spectroscopic evidence (Ono et al 1992;Yachandra et al 1993;Roelofs et al 1996;Bergmann et al 1998;Iuzzolino et al 1998;Dau et al 2001;Messinger et al 2001) but disagree with the suggested low-valent Mn 4 (III,III,III,III ) state (Zheng & Dismukes 1996;Kuzek & Pace 2001).…”
Section: Structural Models Of the O 2 -Evolving Centresupporting
confidence: 49%
“…The earlier analysis by Yachandra and coworkers (17) gave one change of more than 0.2 Å (or one of 0.2 and one of 0.1 Å). This change, supported by results of earlier and later XANES spectra (33), led to the conclusion that an oxygen rather than a manganese is oxidized in this transition, which strongly affected the suggested O-O bond formation mechanism (34,35). The conclusion from the XANES spectra has been questioned experimentally (36), and also recently on the basis of DFT model calculations (37).…”
Section: Resultsmentioning
confidence: 76%
“…A decrease in the fluorescence level after the flash indicates oxidation of the Mn complex, an increase reflects Mn reduction. [We note that the magnitude of ⌬F X-ray is S-state-dependent; for excitation at 6,552.5 eV, it is larger in S 1 3S 2 than in S 2 3S 3 (36)(37)(38).] At 0.2 bar O 2 , Mn reduction was absent on flash 1 and small on flash 2, whereas at 13 bar O 2 , significant Mn reduction occurred already on flash 2.…”
mentioning
confidence: 76%